1995
DOI: 10.1203/00006450-199506000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Birth-Related Up-Regulation of mRNA Encoding Tyrosine Hydroxylase, Dopamine β-Hydroxylase, Neuropeptide Tyrosine, and Prepro-Enkephalin in Rat Adrenal Medulla Is Dependent on Postnatal Oxygenation

Abstract: The transynaptic splanchnic regulation of the adrenal medulla is not functional in the newborn rat. Thus, synthesis and release of adrenal catecholamines and peptides are assumed to be regulated by nonneuronal mechanisms at this stage. In a previous study we reported 4-5-fold increases in the levels of mRNA encoding tyrosine hydroxylase (TH), dopamine P-hydroxylase (DBH), and neuropeptide tyrosine (NPY) in the rat adrenal medulla immediately after birth. In the present in situ hybridization study the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Furthermore, such prenatal Hx is associated with an increased risk for neurologic abnormalities during development (17), including cognitive and behavioral disorders (18 -21). Holgert et al (22) have found that short-term Hx (11-13% O 2 ) during the last 3 d of gestation induces an increase in the level of TH mRNA in the fetal adrenal gland 1 d before birth. However, there are presently no studies available dealing with the effects of longterm Hx on the maturation of the adrenal medulla.…”
mentioning
confidence: 99%
“…Furthermore, such prenatal Hx is associated with an increased risk for neurologic abnormalities during development (17), including cognitive and behavioral disorders (18 -21). Holgert et al (22) have found that short-term Hx (11-13% O 2 ) during the last 3 d of gestation induces an increase in the level of TH mRNA in the fetal adrenal gland 1 d before birth. However, there are presently no studies available dealing with the effects of longterm Hx on the maturation of the adrenal medulla.…”
mentioning
confidence: 99%
“…However, in the rat this regulation is not mature at birth (9,11). Still, CAs are released with hypoxia (3), and synthesis of CA enzymes, and also of ENK and neuropeptide Y, is up-regulated several-fold at birth (5,6). Most likely an O 2 -sensing mechanism in the chromaffin cells plays a regulatory role at this stage (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Slides and 14 C standards [Amersham (20)] were covered with Hyperfilm ␤-max film (Kodak, Rochester, NY, U.S.A.) and exposed at Ϫ20°C for 3 and 7 d. Computerized and digitized quantification of tissue gray levels (256 levels) on the films was performed using a Nikon Microphot FX-microscope (Nikon, Tokyo, Japan), a Macintosh computer equipped with a QuickCapture frame-grabbing board (Data Translation, Marlboro, MA, U.S.A.), and a Dage-MTI 72 CCD series camera (DAGE-MTI, Michigan City, IN, U.S.A.) equipped with a Nikon 55-mm f2.8 lens, and by use of the public domain NIH Image program (http://rsb.info.nih.gov/nih-image/), as described earlier (5,6). Gray levels of the 14 C standards were determined and used in a third-degree polynomial approximation to construct a gray level to activity transfer function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In adult rat, catecholamine secretion in adrenal medulla chromaffin cells is controlled by the cholinergic splanchnic nerve, whereas this innervation is absent at birth (39), meaning that chromaffin cells have the capacity to release catecholamines without neural stimulation during fetal life (9). It has been shown that stress, such as maternal hypoxia during the last 3 days of gestation, induces an increase in the levels of TH and D␤H mRNA in fetal adrenal glands 1 day prior to birth (18). Adrenal hypoxia in the current IUGR model is supported by microarray analysis and quantitative RT-PCR, revealing the upregulation of many genes related to hypoxia, such as Igfbp1, aldolase A, and ceruloplasmin.…”
Section: Discussionmentioning
confidence: 99%